The Role of Local Governments in Supporting Social Forestry Implementation in Indonesia: A Social Network Analysis and Evidence from Eastern Indonesia - Rahayu, Sari; Sakuntaladewi, Niken; Sumirat, Bugi Kabul; Widyaningsih, Tri Sulistyati; Yusnikusumah, Tri Rizkiana; Muin, Nurhaedah; Bisjoe, Achmad Rizal Hak (Forestry Faculty, Universitas Hasanuddin, 2024)
Social forestry has become an integral part of Indonesia's efforts to balance economic development, conservation of natural resources, and the well-being of local communities. The Jokowi administration has made significant efforts to promote this initiative, including allocating 12.7 million hectares of state forest areas and recognizing it as an instrument to address tenure issues in forest areas through the Omnibus Law on Job Creation with getting support from various regulations by relevant ministries. However, social forestry support is needed down to the local government/regional levels (provincial, regency, and village levels). This study aims to analyze the local government’s support for implementing social forestry. We employ Social Network Analysis to identify local government entities and their relationships in implementation processes. Additionally, document analysis is used to assess the extent of local government support through their working documents. The study shows that local government support for the implementation is still limited, with its execution primarily concentrated within a few agencies. Social forestry has not yet fully become a strategy for achieving community well-being around forests, enhancing local economies, or protecting forest resources. Furthermore, stakeholders' understanding of social forestry, resource availability, and local government policies to support it remains limited. Improvements in these three aspects are necessary to ensure successful implementation at the regional levels.